2005
DOI: 10.1080/027868290910224
|View full text |Cite
|
Sign up to set email alerts
|

Particle Emissions from a Small Two-Stroke Engine: Effects of Fuel, Lubricating Oil, and Exhaust Aftertreatment on Particle Characteristics

Abstract: The effects of fuel and lubricating oil formulation and exhaust catalytic aftertreatment on physical and chemical characteristics of two-stroke engine exhaust particles were studied. The exhaust particles were produced with a professional chainsaw engine. The employed fuels were a 98-octane oxygenated, low-sulfur, low-aromatic reformulated gasoline, which served as a reference, and a 95-octane nonoxygenated alkylate gasoline that had no aromatics and olefins. The applied lubricating oils were a semisynthetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 26 publications
1
26
1
1
Order By: Relevance
“…Alander et al 48 found that PM emissions from a single two-stroke chain saw could vary by 4% to 16% even when tested under a single set of operating conditions. When conditions such as presence of a catalyst and fuel type and lubricating oil type were varied, the emissions differed by almost a factor of two.…”
Section: Regional Comparisons Of Emission Estimates With Observedmentioning
confidence: 99%
“…Alander et al 48 found that PM emissions from a single two-stroke chain saw could vary by 4% to 16% even when tested under a single set of operating conditions. When conditions such as presence of a catalyst and fuel type and lubricating oil type were varied, the emissions differed by almost a factor of two.…”
Section: Regional Comparisons Of Emission Estimates With Observedmentioning
confidence: 99%
“…For diesel emission, EC was higher compared to the gasoline vehicle profile. Zn and Ca are additives in motor oil, and Fe is released from brake pads and muffler ablation (Garg et al, 2000;Maykut et al, 2003;Alander et al, 2005;Wahlin et al, 2006;Zhao and Hopke, 2006). The winter contributions were higher than other seasons.…”
Section: Source Identification and Source Profilesmentioning
confidence: 99%
“…Part-load tests were run on an engine and the exhaust gas emission measured, like in other similar tests [13,16]. Fractional distillation characteristics were carried out with test fuels as well as the test for assessing lubrication properties [12].…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, the difference between fuels lies in the fact that in the alkylate petrol produced specifically for two-stroke engines, the lubrication additive is selected and added by the manufacturer company. Alander et al (2005) states that in comparison to the use of regular petrol, the proportions of, for example, CO and HC in the exhaust gas decrease when alkylate petrol for a two-stroke engine is used [13]. Magnusson et al (2000Magnusson et al ( , 2002 draws the conclusion that the exhaust gas emission increases as alkylate petrol is used [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation